Cyclic demand spectrum. - Malhotra, Praveen K. (Earthquake engineering & structural dynamics.)
The seismic response spectrum defines the amplitude of the load, but it does not specify the number of cycles for which the load must be resisted by the structure. The amplitude by itself is not sufficient to evaluate the seismic resistance of a structure, because the structure's strength, stiffness and energy dissipation capacity reduce with an increase in the number of load cycles. This paper presents a cyclic demand spectrum, which, in conjunction with the amplitude spectrum, provides a more complete definition of the seismic load, hence a way to consider the degradation in strength, stiffness and energy dissipation capacity in a rational manner. Similarly to three amplitude parameters (peak ground acceleration, peak ground velocity, and peak ground displacement), three cyclic demand parameters are introduced for stiff, moderately stiff, and flexible systems. A design example is presented to illustrate the use of the cyclic demand spectrum.